Synthesis and characterization of Cu doped CdTe thin films for solar cell application. (2021) - Ray, Subhasmita; Bangera, Kasturi V.; Tarafder, Kartick
Abstract: Synthesis and characterization of thin-film based photovoltaic materials attract with great research interest for the past few years as the efficiency of the photovoltaic cell can be improved systematically with a proper functionalization of the films and making multilayers. We have synthesized Cu-doped CdTe thin films with different doping concentrations using the PVD technique. The structural, morphological, and optical properties of synthesized films were carefully investigated. Our study shows that all the prepared films are polycrystalline with a cubic structure. The morphological studies (SEM) reveal that all the films are crack and pinhole-free. The composition and stoichiometry of the film were confirmed by energy dispersive spectroscopy (EDS) study. The optical characterization of the samples is performed by using UV–VIS -NIR spectrometer. The result shows interesting optical behavior of the film suitable for solar cell applications.